A GENERAL MODEL FOR UNIFICATION OF THE THREE PROCESSES OF SLEEP-WAKE REGULATION - A. A. Putilov; Ye. G. Verevkin (Бюллетень сибирской медицины)
The most-known model of sleep-wake regulation includes different formulae describing the kinetics of three separate processes, i.e., homeostatic, circadian, and ultradian. We tried to explain all these processes within a more parsimonious modeling framework and to use the EEG recordings of baseline night sleep for derivation of the model’s parameters and for prediction of the effects of experimental manipulations with sleep-wake regimen.